Human Circulating T Follicular Helper Cell Subsets in Health and Disease - Ueno, Hideki (Journal of clinical immunology, 2016)
T follicular helper (Tfh) cells are specialized to provide help to B cells and to induce durable antibody response. Our knowledge on the biology of Tfh cells and their contribution to disease has significantly increased in the past decade. In particular, recent discoveries of functionally distinct subsets within circulating Tfh (cTfh) cells in human blood have provided clues to assess the ongoing Tfh responses in healthy subjects after vaccinations and in patients with autoimmune diseases. The immune pathways associated with Tfh cell differentiation in humans are also getting revealed. In this review, I will first summarize the subsets within human cTfh cells, and discuss their alterations in patients with autoimmune diseases. Then I will discuss the mechanisms associated with the aberrant Tfh responses in human autoimmune diseases.